The Human and the Animal: Explanatory Commensurability in Darwin’s The Descent of Man - Espada-Brignoni, Teófilo (Circumscribere International Journal for the History of Science, 2015)
Many authors have proposed the use of Michel Foucault’s work as a theoretical approach to historical and sociological inquiry. This article analyzes Darwin’s The Descent of Man through Foucault’s notion of discourse. The question addressed is: how the human subject is constituted as an object of knowledge. Both objects are constructed through the identification of one with the other, arguing that humans are subjected to the same natural laws that animals and simultaneously, that many human traits are also found in animals. This is showed through a diversity of topics including taxonomy, mind, sociality and morality.